(untitled) (One Health & Risk Management, 2024)
Introduction: Breast cancer is the most widespread form of cancer in women and is a threat to female sexuality, considering the breast’s significance in female sexuality, sexual fulfillment, and attractiveness. Female sexual disorders, that involve issues with sexual desire, attraction, stimulation, orgasm, and genitopelvic pain, are common in midlife breast cancer survivors (BCS). Materials and methods: A systematic and structured search of the English-language literature was conducted using PubMed, SCOPUS, EMBASE, and Web of Science databases to find studies relevant to the targeted issue. After the initial search, 160 items were located. Finally, 30 articles were included in this review. Results: Patients with sexual dysfunctions may benefit from a variety of treatment approaches, such as pharmaceutical, physical, and psychological ones. Evidence shows that local strategies, such as vaginal estrogens and DHEA, vaginal moisturizers, aqueous lidocaine, vaginal dilators, intravaginal laser and radiofrequency, as well as psychotherapeutic strategies, such as cognitive behavioral therapy and couple therapy based on sexual health improve sexual function. Conclusions: Identifying and managing sexual dysfunction demands greater consciousness, interpersonal interaction, and education among community physicians and other related health practitioners. To provide appropriate care and prevent the condition from getting more severe, a systematic evaluation of sexual function in BCS patients may be helpful in early diagnosis of all instances.